Romania : Financial Sector Assessment Program-Technical Note-Macroprudential Policy Framework and Tools. (IMF Staff Country Reports; Country Report, 2018)
This Technical Note analyzes the implementation of macroprudential policy framework and tools in Romania. The National Bank of Romania (NBR) has a long experience in implementing macroprudential policy measures. The NBR monitors several indicators to assess the build-up of systemic risk, many of which are derived from the nation-wide credit register and related data sources. The institutional framework for macroprudential policymaking has recently been revised and contains a clear mandate and well-defined objectives, but NBR's role seems constrained. It is recommended that the macroprudential policy toolkit should be strengthened further to address risks identified in the Financial Sector Assessment Program's risk analysis. The systemic risk buffer should be calibrated carefully to address risks stemming from the strong sovereign-bank nexus.